Trade Policy and Economic Growth in Nigeria - Afolabi, Mutiu Adeniyi (Acta Universitatis Danubius. Œconomica, 2022)
This study examines the effect of trade policy on Nigeria economic growth and used annual data that spanned from 1983 to 2018. The Augmented Dickey-Fuller test revealed that the variables employed have mixed order of integration (i(0),i(1)). Thereafter, An Autoregressive Distributed Lag (ARDL) technique was employed because it suits the outcome of the pre estimation test. A cointegration test among the variables is conducted using the ARDL bound test technique. The ARDL estimates show that adjusted trade ratio impacted positively on GDP both in the short and long run and price based variables impacted positively on GDP both in the short and long run. We computed impulse response function for the estimated ARDL model to confirm the accuracy of Bound testing result. Interestingly, the finding remained robust when the potential effect of the trade policy is accounted for using IRF. The IRF show dynamically that GDP responded positively to trade policy at a higher horizon contrary to the short run estimate thereby given more credibility to the result of the ARDL which was been transformed to IRF. The dynamic responses allow us to find out that GDP responded positively and negatively to trade policy but the accumulated (long run) effect is positive. The study conclude that adjusted trade ratio is procyclical while price based mechanism is countercyclical in Nigeria during the scope of study. The study suggests that the policy makers should adopt policies that can promote innovations and shut out any form of black market premium that can cause distortions.